Auditory perceptual discomfort and low-hearing tolerance in the first episode psychosis - Maria Lúcia de Bustamante Simas; Naianna Ribeiro Mocelin dos Santos; Aline Mendes Lacerda (Psicologia: Reflexão e Crítica, 2022)
Abstract Awareness of perceptual and sensory changes that might occur in visual, auditory, proprioception, and other senses, in the early stages towards the First Episode Psychosis (FEP), and their subsequent sensorial evolution as the disturb progresses deeper into an acute episode, might be a key element for interrupting the process. In the present study, we investigated hearing discomfort/tolerance to 16 given sound streams. Sixteen people diagnosed with FEP, participated in the experiment. Sixteen frequency sweeps varying in modulation envelopes (sawtooth, sine), order (ascending, descending), duration (4s, 8s), and range (50–8000 Hz, 2–8 kHz) were presented randomly, but always in the same sequence, to FEP and healthy controls (HC). The level of discomfort was estimated by the participant by making a mark across a continuous line whose extremes read “nothing bad” (left) and “too bad” (right). Results showed that ascending sine pure frequency sweeps (p < 0.01) and descending sine pure frequencies sweeps (p < 0.01) caused the maximum discomfort in FEP. Other variables also showed differences between FEP and HC, and FEP were always more intolerant to such pure frequency sweeps than HC. We conclude that this might be useful for very early assessment of people at risk, people with FEP, and people with schizophrenia.